Recent Literature Review of Significance of Polypyrrole and Its Biocomposites in Adsorption of Dyes from Aqueous Solution - Rabia Rehman; Asma Raza; Farhat Yasmeen; Amara Dar; Zahrah T. Al-thagafi; Zelalem Meraf (Adsorption Science & Technology)
The usage of dyes has been tremendously augmented due to industrialization and human’s intrinsic fascination with colors. Owing to their excessive usage in industries like textiles, food, cosmetics, paints, printing etc., it is indisputably a contributing factor in aquatic pollution. Dyes effluents have emerged as a burgeoning challenge. Owing to issues such as toxicity, mutagenicity, and disturbed photosynthesis associated with dye contamination, it is crucial to look for an explication to deal with this challenge. Polypyrrole-based biocomposites have been reported as good adsorbents for textile wastewater treatment. In the last decade, numerous studies have stated the effective removal of dyes via Polypyrrole-based biocomposites. This review concentrates on the implication of different Polypyrrole-based biocomposites for decontamination of dyes and synthesis methods, characteristics, and mechanism of dyes degradation by these biocomposites from wastewater.